PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR MATEMATIKA - Ayuni, Juwanti; Wahab, Wahab; Setyaningrum, Vidya (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2024)
This study investigated the effect of the problem-based learning model (PBL) with flashcard media on the mathematics learning outcomes of class VI MIS Al-Mustaqim Sungai Raya students. The study used a quantitative method with an experimental design. The results showed that the PBL model with flashcard media had a significant effect on the students' learning outcomes, both in terms of cognitive and psychomotor skills. The average cognitive pretest score of the experimental class was 57.4, which increased to 82.6 after the PBL model was applied. The average psychomotor pretest score was 60.08, which increased to 88.204 after the PBL model was applied. The independent sample t-test showed that the difference between the learning outcomes of the experimental and control groups was statistically significant (p < 0.05). This suggests that the PBL model with flashcard media is an effective way to improve the mathematics learning outcomes of class VI MIS Al-Mustaqim Sungai Raya students.